Cytomegalovirus esophagitis associated with gastroesophageal reflux disease in an immunocompetent patient: case report - Pozzobon, Cesar Romaro; Pozzobon, Fernanda Manhães; Monteiro, Geysa Bigi Maya; Madeira, Eduardo; Chindamo, Maria Chiara (Brazilian Journal of Case Reports, 2023)
Cytomegalovirus infection has a wide variability of clinical presentations depending on the patient's immunity, ranging from asymptomatic infections in immunocompetent individuals to infections with significant morbidity and mortality in immunocompromised patients. We originally described a clinical case of severe cytomegalovirus esophagitis, confirmed by blood polymerase chain reaction (PCR) test and esophageal biopsy, in a young immunocompetent patient with a long-standing diagnosis of gastroesophageal reflux disease. Clinical improvement occurred only after the initiation of specific treatment with ganciclovir, providing a negative viral load. This report reinforces the importance of ruling out the etiology of cytomegalovirus infection in severe ulcerative esophagitis, even in immunocompetent individuals.